The Architecture of Circulating Immune Cells Is Dysregulated in People Living With HIV on Long Term Antiretroviral Treatment and Relates With Markers of the HIV-1 Reservoir, Cytomegalovirus, and Microbial Translocation - Van de Wijer, Lisa; van der Heijden, Wouter A.; Horst, Rob ter; Jaeger, Martin; Trypsteen, Wim; Rutsaert, Sofie; van Cranenbroek, Bram; van Rijssen, Esther; Joosten, Irma; Joosten, Leo; Vandekerckhove, Linos; Schoofs, Till; et al. (Frontiers in Immunology, 2021)
Long-term changes in the immune system of successfully treated people living with HIV (PLHIV) remain incompletely understood. In this study, we assessed 108 white blood cell (WBC) populations in a cohort of 211 PLHIV on stable antiretroviral therapy and in 56 HIV-uninfected controls using flow cytometry. We show that marked differences exist in T cell maturation and differentiation between PLHIV and HIV-uninfected controls: PLHIV had reduced percentages of CD4+ T cells and naïve T cells and increased percentages of CD8+ T cells, effector T cells, and T helper 17 (Th17) cells, together with increased Th17/regulatory T cell (Treg) ratios. PLHIV also exhibited altered B cell maturation with reduced percentages of memory B cells and increased numbers of plasmablasts. Determinants of the T and B cell composition in PLHIV included host factors (age, sex, and smoking), markers of the HIV reservoir, and CMV serostatus. Moreover, higher circulating Th17 percentages were associated with higher plasma concentrations of interleukin (IL) 6, soluble CD14, the gut homing chemokine CCL20, and intestinal fatty acid binding protein (IFABP). The changes in circulating lymphocytes translated into functional changes with reduced interferon (IFN)- γ responses of peripheral blood mononuclear cells to stimulation with Candida albicans and Mycobacterium tuberculosis. In conclusion, this comprehensive analysis confirms the importance of persistent abnormalities in the number and function of circulating immune cells in PLHIV on stable treatment.